A Recently Discovered Esther Inglis Manuscript. (5th December 2018) - Ziegler, Georgianna
Abstract: In 2016 the Folger Shakespeare Library in Washington, DC acquired a previously unidentified manuscript by Esther Inglis, the seventeenth-century Scottish calligrapher. Now Folger MS V.a.665, it dates from 1612, and was a second gift that year from Inglis to Prince Henry. The main text is a copy of the Psalms in French prose, preceded by a lengthy dedication to the Prince. While the text itself is not decorated, the manuscript includes a self-portrait of Inglis and an image of King David at prayer, and the whole is bound in an embroidered binding which may also be by Inglis. This is the fifth and last manuscript presented by Inglis to Prince Henry, not long before his death in November 1612.